2010
DOI: 10.1364/oe.18.007269
|View full text |Cite
|
Sign up to set email alerts
|

Reflectometer-based metrology for high-aspect ratio via measurement

Abstract: We develop a modified thin film model with adjustable ratio of the illuminated surface areas for accurate reflectivity calculation of deep via structures. We also propose a method combining a half oblate spheroid model and a reflectance modulation algorithm for extraction of via bottom profile from the measured reflectance spectrum. We demonstrate the use and enhancement of an existing wafer metrology tool, spectral reflectometer by implementing novel theoretical model and measurement algorithm for through-sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…We developed a reflectance modulation algorithm for extraction of the via bottom shape from the measured reflectance spectrum. 16 We assume an effective area of the bottom, with a diameter of 2e, that contains depth variations that are sufficiently small and below the resolution limit of depth measurement of the measuring tool. We use a simple method to estimate the measurement resolution from the pixel resolution.…”
Section: Via Bottom Shapementioning
confidence: 99%
See 1 more Smart Citation
“…We developed a reflectance modulation algorithm for extraction of the via bottom shape from the measured reflectance spectrum. 16 We assume an effective area of the bottom, with a diameter of 2e, that contains depth variations that are sufficiently small and below the resolution limit of depth measurement of the measuring tool. We use a simple method to estimate the measurement resolution from the pixel resolution.…”
Section: Via Bottom Shapementioning
confidence: 99%
“…14,15 In our previous studies, we demonstrated the use and enhancement of this existing wafer metrology tool by implementing a novel theoretical model and measurement algorithm for HAR TSV measurements. 16,17 TSV manufacturing process with high etch rate stages combined with efficient passivation or deposition steps have achieved nearly anisotropic shapes, with high etch rates of 5 μm/min or greater. 18,19 Good etch depth uniformity and shape requirements for 3-D integration are necessary in a high-volume manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Several optical techniques can be used for measuring TSV depths, including spectral reflectometry [4][5][6][7][8][9][10][11], backside infrared spectral reflectometry [12][13][14], ellipsometry (for rather shallow trenches) [15], confocal chromatic microscopy [16] and time domain OCT [16][17][18][19], and hybrid systems [19,20]. Time domain OCT, whose principle is sketched in fig.…”
Section: Introductionmentioning
confidence: 99%
“…2, has its strengths in the case of deep TSV of high aspect ratio. It allows scanning a very large range along the optical axis (z-axis), whereby the resolution in z-direction does not depend on the size of the scanned z-interval contrary to spectral reflectometry [4,5]. The interpretation of timedomain OCT interferograms is unambiguous: The order of the detected signals agrees with the order of the reflecting objects along the optical axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation